Acousto-optic systems for advanced microscopy. (24th November 2020) - Duocastella, Martí; Surdo, Salvatore; Zunino, Alessandro; Diaspro, Alberto; Saggau, Peter
Abstract: Acoustic waves in an optical medium cause rapid periodic changes in the refraction index, leading to diffraction effects. Such acoustically controlled diffraction can be used to modulate, deflect, and focus light at microsecond timescales, paving the way for advanced optical microscopy designs that feature unprecedented spatiotemporal resolution. In this article, we review the operational principles, optical properties, and recent applications of acousto-optic (AO) systems for advanced microscopy, including random-access scanning, ultrafast confocal and multiphoton imaging, and fast inertia-free light-sheet microscopy. As AO technology is reaching maturity, designing new microscope architectures that utilize AO elements is more attractive than ever, providing new exciting opportunities in fields as impactful as optical metrology, neuroscience, embryogenesis, and high-content screening.